Simulation and performance analysis of the sub carrier multiplexed radio over fiber system - 618598 Sevia Mahdaliza Idrus Sutan Nameh; Fakulti Kejuruteraan Elektrik (Skudai : Penerbit Universiti Teknologi Malaysia, 2007)
PSZJBL